Digital technologies in the organization of the educational process in the teachers’ training system //Las tecnologías digitales en la organización del proceso educativo en el sistema de formación docente - Vezetiu, Ekaterina V.; Petrishchev, Igor O.; Shubovich, Valery G.; Varnavskaya, Oxana O.; Kutepov, Maxim M. (Revista de la Universidad del Zulia, 2020)
Abstract The current stage of political, economic and social development is characterized by the active introduction of digital technologies, which have become an integral part of society. The education sector has not been on the sidelines. Today, the field of education, including professional, includes the use of various electronic media and resources. The need to build a digital educational space is determined by a series of factors, among which the development of the digital economy and its requirements for the training of specialists predominate. Digital technology has transformed learning and teaching. At the center of the modern stage of technological development for the foreseeable future, smart technologies will continue to play a dominant role. The purpose of the article is to analyze the impact of digital technology on the quality of training of students in continuing education courses. A study among students of continuing education courses has established the impact of digital technology on the quality of training of students of continuing education courses. The essence of digitization in education is highlighted in the article, the details of the digital presentation of information are determined, the characteristics of the implementation of digital technologies are revealed, and their capabilities are noted. Resumen La etapa actual de desarrollo político, económico y social se caracteriza por la introducción activa de tecnologías digitales, que se han convertido en parte integral de la sociedad. El sector de la educación no se ha mantenido al margen. Hoy en día, el campo de la educación, incluida la profesional, incluye el uso de diversos medios y recursos electrónicos. La necesidad de construir un espacio educativo digital viene determinada por una serie de factores, entre los que predominan el desarrollo de la economía digital y sus requisitos para la formación de especialistas. La tecnología digital ha transformado el aprendizaje y la enseñanza. En el centro de la etapa moderna de desarrollo tecnológico en el futuro previsible, las tecnologías inteligentes seguirán teniendo un papel dominante. El propósito del artículo es analizar el impacto de la tecnología digital en la calidad de formación de los estudiantes de cursos de educación continua. Un estudio entre estudiantes de cursos de educación continua ha permitido establecer el impacto de la tecnología digital en la calidad de la formación de los estudiantes de cursos de educación continua. La esencia de la digitalización en la educación se resalta en el artículo, se determinan los detalles de la presentación digital de la información, se revelan las características de la implementación de tecnologías digitales y se señalan sus capacidades.